G30(P) Transcutaneous bilirubin levels >250µmol in the community: feasible and safe pathway with community midwives obtaining heel prick samples for serum bilirubin. (May 2019) - Brighouse, JR; Yoshida, R; Radomska, G; Battersby, C
Abstract : Aims: As recommended by National Institute of Clinical Excellence, community babies with transcutaneous bilirubin (TcB) levels>250µmol have serum bilirubin levels (SBR) performed. In our area, this was performed by the neonatal team. We report the feasibility and safety of a new pathway aimed to avoid unnecessary visits to the unit and improve family experience. Methods: We collected data prospectively over 11 weeks March – May 2018. We compared arrival times (in vs out-of-hours, defined as after 17:30), time between arrival and review, and proportion of babies with SBR threshold requiring phototherapy. Following analysis of initial data, we introduced a pathway where community midwives obtained a heel-prick sample for SBR; brought to the neonatal team by another caregiver (without well baby), together with a new risk-assessment pro forma. We repeated data collection for 6 weeks August – September 2018 and conducted parental feedback surveys. We used chi-squared testing for categorical data and unpaired t-test for continuous data. Results: We included data from 138 babies who presented for jaundice, 80 pre-, and 58 post pathway implementation. Pre- vs. post change: 37 vs. 22 min (t-statistic=0.08, t-critical 1.67 with p=0.05) for average wait from arrival to review; 21% vs. 14% (p=0.839) arriving out of normal working hours; 89% vs. 84% (p=0.919) not reaching SBR threshold for phototherapy. There were no statistically significant differences. Parents felt this change in approach was a 'huge improvement' and was 'much more convenient' by avoiding the need for mother and their well baby travelling to the unit. Conclusion: The majority of well babies with a TcB level above 250µmol do not require phototherapy. We have shown that a pathway in which community midwives perform both TcB and serum sampling, avoiding the need for baby to present to the unit, is feasible and safe and is positively received by family.